Effect of pH on optimization of photofermentative hydrogen production by co-culture of Rhodobacter sphaeroides-NMBL-02 and Bacillus firmus-NMBL-03 - Pandey, A.; Dolly, S.; Semwal, D.; Pandey, A. (Cellular and Molecular Biology, 2017)
Rhodobacter sphaeroides NMBL-02, photosynthetic purple non sulfur (PNS) bacteria and associated Bacillus firmus NMBL-03 were isolated from water sample collected from 15-20 inches beneath the surface of ponds from Northern region of India in modified Sistrom's media (120 ml) containing 3 g/L malate and 1.2 g/L ammonium sulfate. The isolation was done in air tight serum bottles (120 ml) under tungsten bulb (1.8 kLux light intensity) at 30 oC ± 2 oC. The PNS and heterotrophic bacteria associated with the culture was purified by clonal selection method and characterized by 16S rDNA sequencing. The PNS isolate was identified as Rhodobacter sphaeroides NMBL-02 (ID: 1467407, Accession BANKIT: JN256030) and associated heterotroph as Bacillus firmus NMBL-03 (Gene Bank Accession no.: JN 256029). The effect of initial medium pH on optimization of hydrogen production was investigated in batch process. The maximum hydrogen potential and hydrogen production rate was 2310 ± 55 ml/L and 4.75 ml/L culture/h respectively using glutamate (1.7 mmol/L) as nitrogen source and malate (22.38 mmol/L) as carbon source with 76.39% malate conversion efficiency at initial medium pH 5.0. This co-culture has the ability to produce significant amount of hydrogen in the pH range of 5.0 to 10.0 with 76.39% to 35.71% malate conversion respectively.